2020
DOI: 10.1101/2020.04.17.20070318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of medical resource capacities and intensities of public mitigation measures on outcomes of COVID-19 outbreaks

Abstract: One sentence summary: Multiple data sources and cross validation of a COVID-19 3 epidemic model, coupled with a medical resource logistic model, reveal that the key 4 factors that affect epidemic progressions and their outbreak patterns in different 5 countries are the type of emergency medical response to avoid runs on medical 6 resources, especially improved detection rates, the ability to promote public health 7 measures, and the synergistic effects of combinations of multiple prevention and 8 control strat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 9 publications
0
14
2
Order By: Relevance
“…It is worth noting that many studies have demonstrated that media coverage can be considered an effective way to mitigate the spread of disease during the early stages of an outbreak [8,11,19,20]. To further examine the impact of saturation of media coverage and recovery on disease infections, we plotted the cumulative number of the infected individuals during the initial month of the outbreak with various values of α, δ, h 1 and h 2 , as shown in Fig.…”
Section: (C)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that many studies have demonstrated that media coverage can be considered an effective way to mitigate the spread of disease during the early stages of an outbreak [8,11,19,20]. To further examine the impact of saturation of media coverage and recovery on disease infections, we plotted the cumulative number of the infected individuals during the initial month of the outbreak with various values of α, δ, h 1 and h 2 , as shown in Fig.…”
Section: (C)mentioning
confidence: 99%
“…It is known that, facing the emerging or re-emerging infectious diseases, news items surge in a certain period but have saturation due to the fatigue of reporting, and consequently the saturated growth of news items should be considered especially during whole epidemic outbreak. For example, with sharp the increase of COVID-19 cases in mainland China [18,19], information dissemination significantly affected on disease spread via profound psychological/behavioural changes in early 2020, while it has been exhibiting the reporting fatigue recently. Further, with the media impacts, whether the nonlinear recovery induces more complex dynamics, and the detailed contributions of saturated media impact and/or nonlinear recovery to rich dynamics or disease control remain unclear, and hence fall within the scope of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Different mathematical models have been proposed to investigate the spread and dynamics of COVID‐19 since the outbreak of COVID‐19. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 Laxminarayan et at. 1 , 10 , 11 , 12 revealed the transmission pathways and characteristics of COVID‐19 and identified the key factors which affect the contact pattern and the total number of infections.…”
Section: Introductionmentioning
confidence: 99%
“…In the early stage of COVID-19 epidemic, the main research focus is to assess the basic reproductive number, infection scale and the impact of population mobility on COVID-19 transmission [3-6]. With the wide spread of the epidemic, the research focus was quickly shifted to develop and evaluate the effectiveness of control measures[7-11]. The development of COVID-19 vaccinesis accelerated, but the capacity of vaccine production is limited and it may take time to make vaccine available to all the people who are willing to receive it.…”
Section: Introductionmentioning
confidence: 99%